2015
DOI: 10.1515/helia-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Biomorphological Association and Path Analysis in Sunflower (Helianthus annuus L.)

Abstract: In breeding process it is important to know the extent of association between the traits that affect the yield. Objective of this study was to determine genotypic and phenotypic correlation and path coefficients in 50 sunflower hybrid combinations in order to identify research priorities in sunflower breeding. Relationships between seed yield and five bio-morphological traits in sunflower (oil content, protein content, 1,000-seed weight, head diameter and plant height) were studied. Head diameter had the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The highest positive direct effect on seed yield per plant was recorded by number of leaves, stem diameter, head diameter and 100 seed weight (Pandya et al, 2015). According to Jocković et al (2015), the highest direct effect on seed yield was determined for head diameter and oil content, while for protein content and 1000-seed weight the effect was statistically significant. These authors also concluded that higher values of the direct effects of head diameter on seed yield than the values of correlation coefficients indicate that direct selection through this trait on seed yield improvement would be effective.…”
Section: Seed Yieldmentioning
confidence: 91%
“…The highest positive direct effect on seed yield per plant was recorded by number of leaves, stem diameter, head diameter and 100 seed weight (Pandya et al, 2015). According to Jocković et al (2015), the highest direct effect on seed yield was determined for head diameter and oil content, while for protein content and 1000-seed weight the effect was statistically significant. These authors also concluded that higher values of the direct effects of head diameter on seed yield than the values of correlation coefficients indicate that direct selection through this trait on seed yield improvement would be effective.…”
Section: Seed Yieldmentioning
confidence: 91%
“…MARINKOVIĆ et al (2003) estimated a highly significant direct effect of time from seed germination to the end of flowering on seed yield. According to JOCKOVIĆ et al (2015), highest direct effect on seed yield was determined in sunflower for head diameter and oil content, while for protein content and 1000 seed weight the effect was statistically significant.…”
Section: Path Analysismentioning
confidence: 98%